Una nueva especie del género Teucrium L., Sección Polium (Miller) Schreb. (Lamiaceae), para la flora de la Península Ibérica - Crespo, Manuel B.; Mateo, Gonzalo; Navarro, Teresa (Acta Botanica Malacitana, 1994)
.